Animals' Praise of God. (July 2019) - Johnson, Elizabeth
In of the face of mass extinctions, this essay proposes that animals' praise of God is more than a metaphor but an actual event happening in real time without human mediation. To make the case, it explores the God-animal relationship attested in the Bible and contemporary theology, where animals' praise nests within the praise of all creation. The resulting insight gives support to an ecological ethic that aims to keep the song alive.